Co-generation of electricity and syngas on proton-conducting solid oxide fuel cell with a perovskite layer as a precursor of a highly efficient reforming catalyst - Wan, T.; Zhu, A.; Guo, Y.; Wang, C.; Huang, S.; Chen, H.; Yang, G.; Wang, Wei; Shao, Zongping (Elsevier SA, 2017)
© 2017 Elsevier B.V. In this study, a proton conducting solid oxide fuel cell (layered H + -SOFC) is prepared by introducing a La 2 NiO 4 perovskite oxide with a Ruddlesden-Popper structure as a catalyst layer onto a conventional NiO + BaZr 0.4 Ce 0.4 Y 0.2 O 3-δ (NiO + BZCY4) anode for in situ CO 2 dry reforming of methane. The roles of the La 2 NiO 4 catalyst layer on the reforming activity, coking tolerance, electrocatalytic activity and operational stability of the anodes are systematically studied. The La 2 NiO 4 catalyst layer exhibits greater catalytic performance than the NiO + BZCY4 anode during the CO 2 dry reforming of methane. An outstanding coking resistance capability is also demonstrated. The layered H + -SOFC consumes H 2 produced in situ at the anode and delivers a much higher power output than the conventional cell with the NiO + BZCY4 anode. The improved coking resistance of the layered H + -SOFC results in a steady output voltage of ∼0.6 V under a c onstant current density of 200 mA cm −2 . In summary, the H + -SOFC with La 2 NiO 4 perovskite oxide is a potential energy conversion device for CO 2 conversion and utilization with co-generation of electricity and syngas.